2012
DOI: 10.3178/hrl.6.1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial snowfall distribution in mountainous areas estimated with a snow model and satellite remote sensing

Abstract: Abstract:We describe an approach for reconstructing snowfall that combines satellite observations of the snow disappearance date (SDD) with a snow model for two mountainous areas in Japan having distinct snow climatology. This approach allows assessment of the distribution of snow and topographical effects on snowfall within a catchment. We also evaluated how the reconstructed snowfall affects the catchment snow hydrology.Validation at observation sites demonstrated that a combination of the snow model and sno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 21 publications
2
24
0
Order By: Relevance
“…The accumulated snow depth varied from 1.16 to 4.34 m in the north flank, 1.68 to 2.94 m in the south flank and 0.87 to 2.61 m in the central glacier during the study period. More precipitation (snow) at higher altitude could be attributed to the orographic effect, which results in an increase in snow accumulation with elevation [43][44][45][46][47][48] . Correlation coefficients of accumulated snow depth on the north flank, south flank and central glacier with the altitude were found to be 0.78, 0.84 and 0.57 respectively (significant at 1% significance level).…”
Section: Uncertainties In Snow Accumulation On Glaciermentioning
confidence: 99%
“…The accumulated snow depth varied from 1.16 to 4.34 m in the north flank, 1.68 to 2.94 m in the south flank and 0.87 to 2.61 m in the central glacier during the study period. More precipitation (snow) at higher altitude could be attributed to the orographic effect, which results in an increase in snow accumulation with elevation [43][44][45][46][47][48] . Correlation coefficients of accumulated snow depth on the north flank, south flank and central glacier with the altitude were found to be 0.78, 0.84 and 0.57 respectively (significant at 1% significance level).…”
Section: Uncertainties In Snow Accumulation On Glaciermentioning
confidence: 99%
“…Lauscher, 1976;Rohrer et al, 1994;Basist et al, 1994;Sevruk, 1997;Wastl and Zängl, 2008). This strong variability is attributed to the highly complex interaction of the weather patterns with the local topography.…”
Section: T Grünewald Et Al: Elevation Dependency Of Snowmentioning
confidence: 99%
“…Most studies identified a distinctive increase of precipitation with altitude (e.g. Spreen, 1947;Peck and Brown, 1962;Frei and Schär, 1998;Blumer, 1994;Johnson and Hanson, 1995;Roe and Baker, 2006;Liu et al, 2011;Asaoka and Kominami, 2012). Contrary, Blumer (1994), Basist et al (1994) and Arakawa and Kitoh (2011) reported on negative elevation gradients of precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the spatio-temporal patterns of the TLR varied greatly across the different geographical regions of Taiwan. Consequently, the variations of the TLR among the different regions imply that the use of a constant, or socalled standard TLR, such as -6.0 or -6.5°C km -1 (e.g., Willmott and Matsuura 2001; Asaoka and Kominami 2012;Samanta et al 2012) is unjustifiable when predicting full-scale temperatures, especially in complex terrains and under monsoon conditions, as in Taiwan. For example, air temperature of Mt.…”
Section: Regression Formula T = α + β × Ementioning
confidence: 99%